1992
DOI: 10.1002/jlb.52.5.572
|View full text |Cite
|
Sign up to set email alerts
|

Role of CD4+ T lymphocytes and interleukin-5 in antigen-induced eosinophil recruitment into the site of cutaneous late-phase reaction in mice

Abstract: Previous studies suggested that the eosinophil recruitment into the site of cutaneous late-phase reaction (LPR) was dependent on IgE antibody and mast cells. In this study, we determined the role of CD4+ T cells and CD8+ T cells in causing antigen-induced eosinophil recruitment of LPR in mouse skin. Eosinophil infiltration into the subcutaneous tissue of ovalbumin (OVA)-sensitized BALB/c mice was biphasic, reaching the first peak at 6 h after the subcutaneous challenge with OVA and the second peak at 24 to 48 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 30 publications
3
19
0
Order By: Relevance
“…6). As previously reported in other allergic responses, such as airway inflammation and allergic cutaneous responses [22,25,26,27], we propose that in CS responses, IL-5 supports eosinophil production, survival and migration into the local tissue. We also propose that IL-5-dependent maintenance of B-1 cells and rapid early Ag-specific IgM production from B-1 cells are required for CS induction and elicitation.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…6). As previously reported in other allergic responses, such as airway inflammation and allergic cutaneous responses [22,25,26,27], we propose that in CS responses, IL-5 supports eosinophil production, survival and migration into the local tissue. We also propose that IL-5-dependent maintenance of B-1 cells and rapid early Ag-specific IgM production from B-1 cells are required for CS induction and elicitation.…”
Section: Discussionsupporting
confidence: 50%
“…Because IL-5 functions as a chemotactic factor for murine eosinophils [21], IL-5 signals could be required for eosinophils to migrate into the contact Ag-challenged skin. Iwamoto et al [22] have clearly demonstrated eosinophil recruitment into the site of cutaneous late-phase reaction that depends on IL-5. They showed that passive administration of neutralizing anti-mouse IL-5 antibodies suppressed cutaneous eosinophilia reaction induced by ovalbumin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to some investigators, LTR is primarily an IgE-and mast-celldependent reaction (27,28), whereas according to others, LTR mainly corresponds to a CD4 T cell-mediated inflammatory response (29,30). Interestingly, CD4 T cells, particularly Th2 cells, and mast cells have been shown to produce common cytokines, so-called Th2 cytokines including IL-4 and IL-5, in vitro and in vivo (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Those cells are generally believed to mediate the eosinophil accumulation observed during allergic reactions and parasitic infections through a mechanism dependent on IL-5 (Spry 1988, Frew et al 1989, Iwamoto et al 1992. To investigate the putative involvement of lymphocytes on the eosinophil accumulation triggered by LPS the animals were pretreated with cyclosporin A, an inhibitor of T-lymphocyte activation (Borel 1989).…”
Section: Cellular Source Of the Eosinophilotactic Activity Present Inmentioning
confidence: 99%